Process mapping for project execution from the perspective of the purchasing function: Case ABB Power Grids Finland Oy - Kivikko, Emilia (My University, 2020)
Project business is a complex and nonroutine type of business. The features of projects’ affect a lot also to purchasing, demanding flexibility and different ways to support the project execution depending, for example, the features of the different kinds of materials and services that are needed during the project execution. This thesis is conducted for ABB Power Grids Finland Oy and the research question is stated as: What is involved in process mapping for successful pro-ject execution from the purchasing function perspective? The aim of clarifying this is to help the purchasing function to operate more proactive during the project execution process and support the needs of projects’ better considering different purchasing function tasks. The objectives for the thesis are to 1) Identify the different stages of project execution relevant for purchasing. 2) Identify the types of material and services needed in different identified project execution stages. 3) To design the process map. The theoretical framework for the thesis handles the project business features and executing the projects as well as the purchasing responsibilities within the projects. The theory also covers the theory of process mapping to act as a guideline for conducting the actual process map. The theory of project execution covers the basic features of project business and the different ele-ments of it, such as project management, scheduling, material planning, and communication. In the theory of purchasing the purpose of SCM and purchasing is explained and the key features and special needs for project purchases specifically are clarified. Process mapping includes the theory of processes and highlights the importance of high quality in processes in all operations and processes. The chapter offers also more detailed information about the process maps and conducting cross-functional process mapping. The study is conducted as a qualitative case study using data triangulation. The primary data for the study was collected through semi-conducted interviews internally in the case company. In addition to primary data, secondary data such as internal documentation was used to support the primary data findings. In the results of the study, it was possible to identify seven different phases of the project execution process from the beginning of the project until handing over to the customer. Findings revealed that all the phases are important in some way also from the perspective of purchasing function. The purchasing of the materials and services happens mostly during the first three phases of project execution, but the purchasing unit had multiple different kinds of tasks throughout the whole project execution process. The findings of identified phases and materials were presented graphically using a cross-functional flowchart. The process map also included an activity detail sheet which includes general information of the project and RACI chart and SIPOC diagram.

Projektiliiketoiminta on toimialana monimutkainen eikä seuraa tiukkoja rutiineja. Projektien ominaispiirteet vaikuttavat suuresti myös hankintatoimintoihin, joilta vaaditaan joustavuutta ja uusia tapoja tukea projektien toteutusta, riippuen esimerkiksi erilaisista materiaaleista ja palveluista, joita tarvitaan projektin toteutuksen aikana. Tämä tutkielma on toteutettu yritykselle ABB Power Grids Finland Oy ja tutkimuskysymys on: Mitä kuuluu prosessikaavioon onnistuneeseen projektin toteutukseen hankintayksikön näkökulmasta? Tutkimuskysymyksen selventämisen tavoitteena on auttaa hankintayksikköä toimimaan proaktiivisemmin projektien toteuttamisen aikana ja tukea projektien tarpeita paremmin hankintatoimintojen näkökulmasta. Tutkielmalle on asetettu kolme tavoitetta, jotka ovat: 1) Tunnistaa projektin toteutuksen eri vaiheet, jotka ovat merkittäviä hankinnan näkökulmasta. 2) Tunnistaa erilaiset materiaalit ja palvelut, joita tarvi-taan projektin toteutuksen eri vaiheissa. 3) Luoda prosessikaavio. Tutkielman teoreettinen viitekehys käsittelee projektiliiketoiminnalle ominaisia piirteitä ja projektien toteuttamista, kuten myös hankintatoimintojen vastuita projektiliiketoiminnassa. Teoria kattaa myös prosessikaavioihin liittyvän teorian, joka tässä tutkielmassa toimii suuntaviivana itse prosessikaavion luomiselle. Projektiliiketoiminnan teoria kattaa tälle liiketoimintatyypille tyypilliset piirteet ja sen eri osa-alueita kuten projektinhallinta, aikataulutus, materiaalisuunnittelu ja kommunikaatio. Hankintaan keskittyvässä teoriaosuudessa käydään läpi toimitusketjun johtamisen ja hankinnan tarkoitusta, ja selvennetään näiden merkitystä ja tavoitteita erityisesti projektiliiketoiminnassa. Teoria prosessikaavioista sisältää teoriaa prosesseista ja laadun merkityksessä kaikissa toiminnoissa ja prosesseissa. Kappale tarjoaa lisäksi yksityiskohtaisempaa tietoa prosessikaavioista. Tutkimus on toteutettu laadullisena toimintatutkimuksena, käyttäen apuna aineistotriangulaatiota. Ensisijainen aineisto kerättiin puolistrukturoiduilla haastatteluilla yrityksen sisällä. Toissijaista aineistoa, kuten yrityksen sisäistä dokumentaatiota, käytettiin tukemaan ensisijaista ai-neistoa. Tutkimuksen lopputuloksena kyettiin tunnistamaan seitsemän eri projektien toteutuksen vaihetta projektien aloituksesta asiakkaalle luovutukseen. Löydökset osoittivat, että kaikki vaiheet ovat omalla tavallaan tärkeitä myös hankinnan näkökulmasta. Materiaalien ja palveluiden hankinnat painottuvat kolmeen ensimmäiseen projektien toteutusvaiheeseen mutta hankintayksiköllä on myös monia muita erilaisia tehtäviä koko projektin toteutusprosessin ajan. Tulokset esitettiin graafisessa muodossa prosessikaaviona, jossa vastuualueet on eroteltu. Prosessikaavion lisäksi luotiin sivu, joka sisältää yleistietoa, vastuullisuustehtävämatriisin (RACI) ja arvovirtakartan (SIPOC), jotka sisältävät vaihekohtaista tietoa prosessikaaviosta
Keywords: fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master's Programme in Industrial Management